2010
DOI: 10.1111/j.1365-2966.2009.15870.x
|View full text |Cite
|
Sign up to set email alerts
|

The scattering and extinction properties of nanodiamonds

Abstract: The study of scattering and extinction properties of possible nanodiamond grains in the ISM are reported. Calculations using Discrete Dipole Approximation (DDA) for varying ellipsoidal shapes and sizes from 2.5 to $10 nm$ are considered. Nanodiamonds show negligible extinction from IR to near-UV and very sharp far-UV rise. Comparison with observations rule out possibility of independent nanodiamond dust but point towards possibility of nanodiamonds as a component in the ISM. Radiation induced transformations m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 73 publications
(136 reference statements)
0
14
0
Order By: Relevance
“…These sightlines are in general carbon‐rich, having traces of carbonaceous molecules (Roueff et al 2002; Oka et al 2003; Ádámkovics, Blake & McCall 2005); hence the silicate fraction along these sightlines could be lower than the average Galactic abundance. Incorporating other carbonaceous materials supposed to be present in the ISM, namely organic refractory carbon (Li & Greenberg 1997), PAH (Draine & Li 2007), bucky onions (Chhowala et al 2003; Li et al 2008), carbon nanoparticles (Schnaiter et al 1998), nanodiamonds (Van Kerkhoven, Tielens & Waelkens 2002; Binnette et al 2005; Rai & Rastogi 2010), etc., seems more suitable for modelling extinction along these objects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These sightlines are in general carbon‐rich, having traces of carbonaceous molecules (Roueff et al 2002; Oka et al 2003; Ádámkovics, Blake & McCall 2005); hence the silicate fraction along these sightlines could be lower than the average Galactic abundance. Incorporating other carbonaceous materials supposed to be present in the ISM, namely organic refractory carbon (Li & Greenberg 1997), PAH (Draine & Li 2007), bucky onions (Chhowala et al 2003; Li et al 2008), carbon nanoparticles (Schnaiter et al 1998), nanodiamonds (Van Kerkhoven, Tielens & Waelkens 2002; Binnette et al 2005; Rai & Rastogi 2010), etc., seems more suitable for modelling extinction along these objects.…”
Section: Introductionmentioning
confidence: 99%
“…a shift towards shorter wavelength that is accompanied by a steep FUV rise. Nanodiamond (ND) extinction shows a steep rise in FUV beyond (Binnette et al 2005; Rai & Rastogi 2010) and considering ND as the core inside a graphite or AMC mantle lowers the bump and shifts the 217.5‐nm peak blueward (Rai & Rastogi 2008, 2010). There is a profile similarity of extinction incorporating NDs inside carbonaceous material with observations along non‐CCM sightlines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also hinted by the numerical tendency during the fitting procedure to go below the lowest limit of 5 nm in particle size, that is systematic for all the lines of sight in the MWG and in the MCs. Such small particles might be carbon mantle fragments, possibly produced during some destructive events (as discussed in the previous paragraph), such as e. g. nanodiamonds (Rai & Rastogi 2010Rai & Botet 2014).…”
Section: (23)mentioning
confidence: 99%
“…Several works showed that one feasible component with the required properties would be a carbonaceous material in which carbon has an sp 3 structure, such as nanodiamonds or hyperhydrogenated PAHs (see e.g. Rai & Rastogi 2010).…”
Section: Including Actual Pah Cross-sections In Extinction Models?mentioning
confidence: 99%